2009
DOI: 10.1364/oe.17.019739
|View full text |Cite
|
Sign up to set email alerts
|

Cavity design and characteristics of monolithic long-wavelength InAs/InP quantum dash passively mode-locked lasers

Abstract: By extending the net-gain modulation phasor approach to account for the discrete distribution of the gain and saturable absorber sections in the cavity, a convenient model is derived and experimentally verified for the cavity design of two-section passively mode-locked quantum dash (QDash) lasers. The new set of equations can be used to predict functional device layouts using the measured modal gain and loss characteristics as input. It is shown to be a valuable tool for realizing the cavity design of monolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Deconvolved pulses down to 1.2 ps were observed after compensation of the GDD and 1.7 time bandwidth product. Similar results were also achieved from two-section InAs/InGaAlAs Qdash laser by Lin et al [293] who demonstrated 12.3 and 18.4 GHz repetition rates from 3.4 and 2.3 mm long devices, respectively, emitting at 1.59 µ m. In general, lower average output powers due to low drive current besides the inability to attain wider spectral bandwidth render the two-section mode-locked laser applications compared to the single section device …”
Section: Two-sectionsupporting
confidence: 82%
“…Deconvolved pulses down to 1.2 ps were observed after compensation of the GDD and 1.7 time bandwidth product. Similar results were also achieved from two-section InAs/InGaAlAs Qdash laser by Lin et al [293] who demonstrated 12.3 and 18.4 GHz repetition rates from 3.4 and 2.3 mm long devices, respectively, emitting at 1.59 µ m. In general, lower average output powers due to low drive current besides the inability to attain wider spectral bandwidth render the two-section mode-locked laser applications compared to the single section device …”
Section: Two-sectionsupporting
confidence: 82%
“…1,2 Several unique characteristics of quantum dot ͑QD͒ materials, such as ultrabroad bandwidth, ultrafast gain dynamics, and easily saturated gain and absorption, make them an ideal choice for semiconductor monolithic MLLs. [3][4][5] The rf linewidth, which directly influences the phase noise spectral density, is directly related to the integrated rms timing jitter in a semiconductor passive MLL. 6 Thanks to the lower threshold current density and the lower associated spontaneous emission noise in QD laser devices compared to their quantum well ͑QW͒ counterparts, the rf linewidth is generally narrower in a passive QD MLL.…”
mentioning
confidence: 99%
“…19 Results showed that, given the laser geometry, mode-locking should indeed happen with the working conditions used to obtain the results reported in this paper. The investigation is still ongoing for the 1-mm laser.…”
Section: Passive Mode-locking: Results and Discussionmentioning
confidence: 54%